The using possibility of full fat sunflower seed in japanese quail diets - Cavit Arslan; Fatma İnal; Mustafa Garip (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine to tull fat sunflower seed supplementation in Japanese quail diets 0, 10, 20 and 30 % on growth performance, carcass characteristic, egg production and quality, hatchery traits. The research was conducted two experiment. In experiment I, totally 224 (one day old) quail were used. Quails were fed containing 0, 10, 20 and 30 % with full fat sunflower seed in ration during 6 weeks. Live weight in groups were found 164.22. 170.60, 169.57 and 175.72 g (p>0.05) carcass weight 115.09. 116.32, 115.94 and 114.06 g respectively (P>0.05). In experiment II. totally 120 (45 days old) quail were used. 0, 10. 20 and 30 % full fat sunllower seed added ration. At the end of the 15 weeks ol research, there were no significant differences between control and experiment groups about egg production. Feed intake in groups were lound 24.56, 24.41, 24.40, 24.46 g. There weren't significant differences between groups respects of fertility, hatchery, hatchability of fertilizing eggs and, late embryonic died (P>0.05). Based in this study, it was concluded that in fattening and breeding quail rations 10, 20 and, 30 % level sunllower seed can addition without any adverse effect on performance.